In vivo study of novel nanocomposite for prostate cancer treatment - Silveira, C. P.; Paula, A. J.; Apolinário, L. M. [UNESP]; Fávaro, W. J. [UNESP]; Durán, N. (IOP Publishing, 2015)
Because of high occurrence of side effects of conventional anticancer drugs, new therapies have been widely studied, such as the use of non-usual molecules and the association with nanomaterials. In this context, sildenafil is a molecule that has been lately considered as a co-adjuvant in cancer therapy because it inhibits an enzyme with a potential role in tumor progression, phosphodiesterase-5. Taking into account the combination of nanoparticles and sildenafil, we produced systems based on mesoporoussilica nanoparticles, Pluronic F-127 and sildenafil as the main therapy for prostate cancer.